Del Nido cardioplegia in the setting of minimally invasive aortic valve surgery. (March 2017) - Vistarini, Nicola; Laliberté, Eric; Beauchamp, Philippe; Bouhout, Ismail; Lamarche, Yoan; Cartier, Raymond; Carrier, Michel; Perrault, Louis; Bouchard, Denis; El-Hamamsy, Ismaïl; Pellerin, Michel; Demers, Philippe
The purpose of this study is to report our experience with del Nido cardioplegia (DNC) in the setting of minimally invasive aortic valve surgery. Forty-six consecutive patients underwent minimally invasive aortic valve replacement (AVR) through a "J" ministernotomy: twenty-five patients received the DNC (Group 1) and 21 patients received standard blood cardioplegia (SBC) (Group 2). The rate of ventricular fibrillation at unclamping was significantly lower in the DNC group (12% vs 52%, p=0.004), as well as postoperative creatinine kinase-MB (CK-MB) values (11.4±5.2 vs 17.7±6.9 µg/L, p=0.004). There were no deaths, myocardial infarctions or major complications in either group. Less postoperative use of intravenous insulin (28% vs 81%, p<0.001) was registered in the DNC group. In conclusion, the DNC is easy to use and safe during minimally invasive AVR, providing a myocardial protection at least equivalent to our SBC, improved surgical efficiency, minimal cost and less blood glucose perturbations.